Social Movement as Subject of Socio-Psychological Analysis - Koval, Hennadiy (Psychological Prospects Journal, 2018)
The problem of the place a social movement within the socio-psychological taxonomyobjects of socio-psychological analysis has been considered in the article.The opposition of the understanding the social movement as a type of group or as a separate class of social phenomena have been indicated. The problem of differentiation of the notion the social movement within the taxonomy of large social groups as a problem of distinguishing social movement from spontaneous groups has been considered. The problem of differentiation of social movement as an organization from the taxonomy of small groups has been considered.The criterions for distinguishing objects of social-psychological taxonomy as different ways of imparting a commonality within the limits of one or another form of social phenomena have been proposed. The differentiation various types of personality characteristics as parameters of possible accedence to one form or another of a social phenomenon have been proposed as the method of the imparting a commonality. It has been proposed to introduce an additional classification criterion for finding the place of social movement within the taxonomy of large organized groups. The notion of the social task as a factor of the organizing of the social movement has been proposed as the additional criterion. It was proposed the understanding of the social movement as a large organized group what is connect by a particular type of social bond and the criterion differentiation of which is the notion of the social task as a set of social conditions and goals of collective activity.The problem of non-detected of factors that determine the relationship between representatives of the public movement has been marked. It’s detect of this problem also involves the disclosure of the motivational substructure of activity which is not included in the structure of the social task.